SCALE MORPHOLOGY OF THREE TELEOSTS (ETROPLUS SURATENSIS, ANABAS TESTUDINEUS, SARDINELLA LONGICEPS) WITH REFERENCE TO FUNCTION - Prakasam, V R; Johnson, Pius (Indian Journal of Fisheries, 2011)
Morphological study showed that the scales of Anabas testudineus are ctenoid, those of Sardinellalongiceps are cycloid and both types of scales occur in Etroplus suratensis. In Anabas and Etroplus, thecirculi are concentric in the submerged portion and they possess serrations, hitherto unreported, whichmay aid in anchoring the scale in its pocket. The circuli are discontinuous and tubular in the exposed portionof scales of Etroplus, whereas in Anabas they are not tubular but are uninterrupted by the formationof spines. In contrast, the circuli of Sardinella are either concentric or parallel, continuous or discontinuousand serrations are absent. In Etroplus and Anabas the radii are found only in the submerged areas.The radii, found in both exposed and submerged portions of Sardinella scales, are horizontal and transverse.They are also canal-like in certain scales. The average number of radii in Etroplus is 11.69 and it doesnot vary with increase in size of the fish, but in Anabas it is 23.42 and shows a linear rise with increasein total length of fish thereby making it possible to back-calculate the length of fish from the number ofradii. It is suggested that radii may function in the capillary flow of water or mucus and that the cteniimay serve a defensive function. The nature of tubular circuli and canal like radii are described.